Characterization of Subtype H6 Avian Influenza A Viruses Isolated From Wild Birds in Poyang Lake, China - Wan, Zhimin; Kan, Qiuqi; Zhao, Zhehong; Shao, Hongxia; Deliberto, Thomas J.; Wan, Xiu-Feng; Qin, Aijian; Ye, Jianqiang (Frontiers in Veterinary Science, 2021)
Subtype H6 avian influenza A viruses (IAVs) are enzootic and genetically diverse in both domestic poultry and wild waterfowl and may cause spillovers in both pigs and humans. Thus, it is important to understand the genetic diversity of H6 IAVs in birds and their zoonotic potential. Compared with that in domestic poultry, the genetic diversity of H6 viruses in wild birds in China has not been well-understood. In this study, five H6 viruses were isolated from wild birds in Poyang Lake, China, and genetic analyses showed that these isolates are clustered into four genotypes associated with reassortments among avian IAVs from domestic poultry and wild birds in China and those from Eurasia and North America and that these viruses exhibited distinct phenotypes in growth kinetics analyses with avian and mammalian cells lines and in mouse challenge experiments. Of interest is that two H6 isolates from the Eurasian teal replicated effectively in the mouse lung without prior adaptation, whereas the other three did not. Our study suggested that there are variations in the mammalian viral replication efficiency phenotypic among genetically diverse H6 IAVs in wild birds and that both intra- and inter-continental movements of IAVs through wild bird migration may facilitate the emergence of novel H6 IAV reassortants with the potential for replicating in mammals, including humans. Continued surveillance to monitor the diversity of H6 IAVs in wild birds is necessary to increase our understanding of the natural history of IAVs.